"The greedy I that gives"—The paradox of egocentrism and altruism: Terror management and system justification perspectives on the interrelationship between mortality salience and charitable donations amid the COVID‐19 pandemic. Issue 1 (31st May 2021) - Jin, S. Venus; Ryu, Ehri
Abstract: Why do people give and help others in face of their own mortality salience? The existential struggle with the awareness of death impacts the gamut of human cognition, emotion, and behavior. This multi‐method research (∑ N  = 1, 219) explains the psychosocial impact of COVID‐19‐related mortality salience on altruism. Drawing from terror management theory, two studies tested death‐thought accessibility, mortality salience, and anxiety buffer hypotheses. Study 1 (cross‐sectional survey), using structural equation modeling, confirms death anxiety and fear are predictors of powerlessness and materialism which, in turn, predict charitable donations. Study 2 (between‐subjects experiment) confirms the causal effects of COVID‐19‐induced mortality salience on altruism. Controlling income and socioeconomic status, people in the mortality salience treatment condition indicate greater monetary donations ($), ratio of prosocial (altruistic) to proself (egocentric) spending (%), donation of time (hour), monetary valuation of time (hourly rate = $/hour), and economic value of donated time (hourly rate*hour) than the controls. These effects are mediated by powerlessness. Moderating effects of relevant individual difference factors are significant: the greedier, more selfish, narcissistic, materialistic, and system‐justifying the donor is, the higher monetary donations, volunteer time, and perceived value of donated time are, only when the COVID‐19‐induced mortality is made salient but not in the controls. Environmental and dispositional factors jointly influence vulnerability to mortality salience. The paradox of egocentrism and altruism, as an evolutionarily adaptive protective buffer against existential insecurity for social and cultural animals, can help revitalize resilience, thus shedding some lights on the sociopsychological mechanism of consumers' subjective well‐being. Implications for consumer affairs, social marketers, and policymakers are discussed.